Bitterness and antibacterial activities of constituents from Evodia rutaecarpa - Xiaoguang Liang; Bo Li; Fei Wu; Tingzhao Li; Youjie Wang; Qiang Ma; Shuang Liang (BMC, 2017)
Abstract Background Bitter herbs are important in Traditional Chinese Medicine and the Electronic Tongue (e-Tongue) is an instrument that can be trained to evaluate bitterness of bitter herbs and their constituents. The aim of this research was to evaluate bitterness of limonoids and alkaloids from Evodia rutaecarpa to demonstrate that they are main bitter material basic of E. rutaecarpa. Methods Nine compounds, including limonoids, indoloquinazoline alkaloids and quinolone alkaloids, were isolated, identified and analyzed by the e-Tongue. Additionally, the antibacterial activities of the nine compounds were evaluated against E. coli and S. aureus. Results All the nine compounds had bitter taste and antibacterial activities to some extent. Among them, limonoids, which were the bitterest compounds, had greater antibacterial activities than alkaloids. And there is a positive correlation between bitter taste and antibacterial activities. Conclusions It was confirmed in our study that limonoids, indoloquinazoline alkaloids and quinolone alkaloids are main bitter material basic of E. rutaecarpa based on two evaluation methods of e-Tongue and antibacterial experiment. In addition, the e-Tongue technique is a suitable new method to measure bitter degree in herbs.